2016
DOI: 10.1007/s00382-016-2992-z
|View full text |Cite
|
Sign up to set email alerts
|

The Bjerknes feedback in the tropical Atlantic in CMIP5 models

Abstract: for the error in seasonality. The third component of the BF, the impact of HC' on SST' in the eastern part of the basin, deviates from what we find in reanalysis. We find an influence of HC anomalies on overlying SSTs in the eastern equatorial TA, but it is weaker than in the reanalysis and it is not strongly confined to the equator. Longitude-depth cross sections of equatorial temperature variance and correlation between subsurface temperature anomalies and SST' in the cold tongue region show that flawed simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
69
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 29 publications
9
69
0
1
Order By: Relevance
“…Our results agree with the observations-based part of Deppenmeier et al (2016)'s analysis of the Bjerknes feedback in the tropical Atlantic. However, while Deppenmeier et al (2016) point out that it is mainly the relationship between upper ocean heat content (approximated by our SSH) and SST that is too weak in CMIP5-simulations, the KCM's problems are mainly related to the SST-u10 relationship, possibly due to the low atmospheric vertical resolution.…”
Section: Feedback Strengths In the Tropical Atlanticsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results agree with the observations-based part of Deppenmeier et al (2016)'s analysis of the Bjerknes feedback in the tropical Atlantic. However, while Deppenmeier et al (2016) point out that it is mainly the relationship between upper ocean heat content (approximated by our SSH) and SST that is too weak in CMIP5-simulations, the KCM's problems are mainly related to the SST-u10 relationship, possibly due to the low atmospheric vertical resolution.…”
Section: Feedback Strengths In the Tropical Atlanticsupporting
confidence: 91%
“…In agreement with Keenlyside and Latif (2007) and Deppenmeier et al (2016), all observed feedback elements are generally strongest in early boreal summer, establishing a closed Bjerknes feedback loop in May-July (Fig. 10a).…”
Section: Feedback Strengths In the Tropical Atlanticsupporting
confidence: 78%
See 1 more Smart Citation
“…Several studies have demonstrated that even though weaker than in the Pacific, the Bjerknes feedback is active in the equatorial Atlantic [e.g., Zebiak, 1993;Keenlyside and Latif, 2007;Lübbecke and McPhaden, 2013;Deppenmeier et al, 2016]. Other mechanisms that have been discussed involve meridional advection of temperature anomalies [Richter et al, 2013], forcing from equatorial deep jets [Brandt et al, 2011b], and heat flux forcing [Nnamchi et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the Atlantic Niño is widely believed to be dynamically driven because of the Bjerknes feedback (Zebiak 1993;Keenlyside and Latif 2007;Lübbecke and McPhaden 2013;Deppenmeier et al 2016), equatorial Kelvin waves (Brandt et al 2011), and meridional temperature advection from the tropical North Atlantic Ocean (Richter et al 2013).…”
Section: Introductionmentioning
confidence: 99%